Etika Guru dalam Perspektif al-Timidzi (Studi Atas Kitab Sunan al-Tirmidzi Karya Abu Isa Muhammad Bin Isa al-Tirmidzi) - Ahmad Junaedy Abu Huraerah (Institut Agama Islam Negeri (IAIN) Manado, 2016)
This paper is a hadith study on the concept of teachers' ethics according to Abu Isa al-Tirmidzi in his Sunan book. This concept is very relevant to the professionalism of the Islamic religious education teachers, as stated by the Law No.14 of 2005 on Teachers and Lecturers. In Islamic education, teachers have important meaning and roles, because not only that they have a responsibility, and determine the direction of education, they are also central in shaping individual Muslims to be in line with the educational goals of Islam. Therefore, Islam highly appreciates and respects the people who are knowledgeable and working as educators. Islam elevates and glorifies them more than other Muslims who have no knowledge and not educators. In order to obtain that award and honor, they, in the process of teaching, should observe good ethics. A teacher must possess honesty, humility, transparency in the teaching of science, and has no favoritism.Keywords: Teachers’ ethics, al-Tirmidzi, Islamic education